The effect of oxide precipitates on minority carrier lifetime in p-type silicon - Murphy, J; Bothe, K; Olmo, M; Voronkov, V; Falster, R (2011)
Transient and quasi-steady-state photoconductance methods were used to measure minority carrier lifetime in ∼10 cm p-type Czochralski silicon processed in very clean conditions to contain oxide precipitates. The nucleation and growth times for precipitation were varied to produce 35 samples, which were then characterised by chemical etching and transmission electron microscopy to determine the density and morphology of the precipitates. The effects of other known recombination mechanisms (band-to-band, Coulomb-enhanced Auger, iron-related, and boron-oxygen related) were factored out to isolate the lifetime component associated with the precipitates as accurately as possible. In the samples processed to contain mainly unstrained precipitates, it was shown that the lifetime component due to the precipitates could be extremely high (up to ∼4.5 ms). Recombination at unstrained precipitates is weak and it is estimated that the capture coefficient lies between 3 × 10 -8 cm 3 s -1 and 1.3 × 10 -7 cm 3 s -1 at an injection level corresponding to half the doping level. Strained precipitates act as strong recombination centres with a capture coefficient of ∼1 × 10 -6 cm 3 s -1 at the same level of injection. For the samples investigated, the effective capture coefficient is increased by a factor of ∼3 to 4 when other extended defects (such as dislocations and stacking faults) accompany the strained precipitates. The shape of the injection level dependence of lifetime was similar for all the specimens studied, with the magnitude of the lifetime being dependent on the precipitate density and strain state but approximately independent of precipitate size. © 2011 American Institute of Physics.